(untitled) - Baehr, Hans Dieter (Berlin, 1998)
In the first chapter, which contains the basic concepts and fundamental laws of heat and mass transfer. The student obtains an overview of the different modes of heat and mass transfer, and learns at an early stage how to solve practical problems and to design heat and mass transfer apparatus.
Keywords: Heat,Mass transfer; Transmission